An integrated tool to improve the safety of seaports and waterways under strong wind conditions. Issue 234 (March 2023) - Ricci, A.; Vasaturo, R.; Blocken, B.
Abstract: The expanding capacity of seaports for worldwide competitiveness is leading to an increased risk exposure. The increasing ship size causes larger wind forces that can render ship navigation difficult in stormy weather. The alert system for the suspension of port operations is usually based on the wind conditions measured by anemometers installed ( i ) on top of cranes/buildings often sheltered for some wind sectors; hence unable to provide reliable wind statistics, ( ii ) at undisturbed positions (far from quays); hence unable to catch the actual wind near cranes/mooring ships. Despite many efforts towards the safety management of seaports and waterways, the prediction of real-time local wind conditions in such environments is still challenging. The goal of this paper is the innovative development of an integrated tool to transfer the measured wind field (by on-site measurements) from an undisturbed position to the sea lock under investigation by transfer coefficients computed with CFD. The tool allows tugboat pilots to check in real-time the mean wind speed, wind direction and turbulence intensity in the newly built IJmuiden sea lock, in the Netherlands. This project is targeted at improving the awareness of risks and the prevention of detrimental accidents in seaports in stormy weather. Graphical abstract: Image 1 Highlights: The expanding capacity of ports worldwide is leading to an increased risk exposure. Increasing ship size causes larger wind forces. Knowledge of local wind conditions in seaports is essential for safe ship maneuvering. An integrated tool based on CFD and real-time on-site measurements is developed. The tool can improve the awareness of risks to prevent accidents in seaport areas.